2021
DOI: 10.3389/fmicb.2021.707330
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Antibiotic Resistance in Hospital-Acquired Infections: Current State and Emerging Technologies in Disease Prevention, Diagnostics and Therapy

Abstract: Rising antibiotic resistance is a global threat that is projected to cause more deaths than all cancers combined by 2050. In this review, we set to summarize the current state of antibiotic resistance, and to give an overview of the emerging technologies aimed to escape the pre-antibiotic era recurrence. We conducted a comprehensive literature survey of >150 original research and review articles indexed in the Web of Science using “antimicrobial resistance,” “diagnostics,” “therapeutics,” “disinfection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 184 publications
1
46
0
Order By: Relevance
“…This finding is in harmony with the former findings, which indicated that K. pneumoniae was the most frequently isolated strain from patients treated in hospitals (2). Moreover, several studies indicated that hospitals and/or clinics are the potential sites for emerging MDR bacterial strains (29,30). Bacteriophages are promising alternative therapeutic agents against multidrug-resistant bacterial pathogens (31).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in harmony with the former findings, which indicated that K. pneumoniae was the most frequently isolated strain from patients treated in hospitals (2). Moreover, several studies indicated that hospitals and/or clinics are the potential sites for emerging MDR bacterial strains (29,30). Bacteriophages are promising alternative therapeutic agents against multidrug-resistant bacterial pathogens (31).…”
Section: Discussionsupporting
confidence: 82%
“…Decreasing the time from obtaining samples for analysis to getting results could help in facilitating earlier initiation of treatment for HAIs in general. The development of "rapid antimicrobial susceptibility testing" (RAST) provides AST results within hours [54], but a number of other methods are being developed and used with equal reduction in time to results [55,56]. Such practices must become the gold standard in our laboratories, as earlier initiation of effective therapy significantly improves patient outcomes [57].…”
Section: Discussionmentioning
confidence: 99%
“…The rising antimicrobial resistance of recent years poses a major threat to humanity and rapid diagnostic tools for bacterial infections are urgently needed ( Avershina et al, 2021a ). The current state-of-the-art in infection diagnostics are mostly based on biochemical analysis of cultured clinical samples ( Vasala et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%